Low Interest in Reading of Students Management Major at Widyatama University - Boga Kuswara, Galuh; Nugraha, Ucu; Lisdayanti, Annisa (International Journal of Psychosocial Rehabilitation, 2020)
Widyatama University is a source of research to find out the influence of brand images of the Department of Management students at Widyatama University and the store atmosphere of the Widyatama University Library in determining the reading interest of Management Department students at Widyatama University. The management department has the highest number of students, and the library facility has an A of accreditation rating, but the drop in visits by management department students creates a gap between these variables. The steps applied in this study use descriptive and verification methods, with a total population of Management Department students at Widyatama University. The withdrawal of a sample of 115 respondents concluded that the management department's image did not significantly influence the reading interest of management department students. However, other partial influences, such as the Store Atmosphere Library, can determine a greater interest than simultaneously with the image of the management department in influencing the reading interest of management department students at Widyatama University.